Economic Costs of the Application of Pesticides on Vegetables in Bardhaman West Bengal-An Emprial Analysis - Roy, Arnab (Indian Journal of Hill Farming, 2019)
The role of pesticides on vegetables has become censoriously important with transformation of Indian agriculture. Modernization of agriculture suggests augmented use of modem inputs. An comprehensive and inclusive study encouraged this investigation of the complex of economic costs consequential from the excessive dependence on pesticides on vegetables. Regardless of the pervasive application of pesticides on vegetables at recommended dosages,pests (insects, plant pathogens, and weeds) destroy 37% of all potential crops. Tomato, cabbage and brinjal, okra and leafy vegetables are important crops for small-scale farmers and migrants in the rural and peri-urban areas of West Bengal. Though pesticides are normally profitable in agriculture, their use does not always decrease crop losses. Expenditures on pesticides by Farmer are below the economic optimum level in most of the vegetables, and the estimated function for injury reduction shows that amounts of pesticide are significantdeterminants of leafy vegetables yields only. Stochastic budget analysis also indicates a higher rate of return to vegetable production with the use of resistant seeds relative to status quo, even considering the technology transfer fee for GM seeds.